2012
DOI: 10.2174/187153012803832594
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Potential of VIP by Modified Pharmaco-kinetics and Delivery Mechanisms

Abstract: Vasoactive intestinal peptide (VIP) conveys various physiological effects in the digestive tract, nervous and cardiovascular system, airways, reproductive system, endocrine system, and more. A family of specific membrane bound receptors, termed VPAC1, VPAC2, and PAC1, bind VIP and trigger the effects. Many of them are of clinical interest. To date more than two thousand publications suggest the use of VIP in diseases like asthma, erectile dysfunction, blood pressure regulation, inflammation, endocrinology, tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…CGRP regulates inflammation and promotes epithelial repair [ 75 ]. Indeed, the current development of VIP-based bronchodilatory drugs that overcome VIP's short half-life indicates that the neuropeptide research remains an option [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…CGRP regulates inflammation and promotes epithelial repair [ 75 ]. Indeed, the current development of VIP-based bronchodilatory drugs that overcome VIP's short half-life indicates that the neuropeptide research remains an option [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles, as sustained-release carriers, can slowly release VPAC2-selective agonists to maintain their effective concentration in patients and continually stimulate insulin secretion without causing hypotension and other potential side effects caused by current drug candidates, which are related to infusion rate and high dose ( 75 , 76 ). Nanoparticle conjugation with VPAC2-selective agonists can not only prolong the half-lives but can also facilitate a targeted drug delivery to improve drug efficacy ( 74 , 77 ). Selenium nanoparticles (SeNPs) have been proven to delay the progression of diabetes owing to their antioxidant properties ( 78 , 79 ).…”
Section: Application Of Nanoparticles On Vpac2-selective Agonistsmentioning
confidence: 99%
“…We selected studies via PubMed search and evaluated references identified in key reviews. 2,3,6,[13][14][15] To limit the scope to those with the greatest translational potential, we included only articles published within the last 10 years. Furthermore, we included only studies assessing nanoformulations in vivo, including 1 patient study (Table S2).…”
Section: Reviewmentioning
confidence: 99%